2016
DOI: 10.1002/14651858.cd004870.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for neck disorders

Abstract: The editorial group responsible for this previously published document have withdrawn it from publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 127 publications
0
4
0
Order By: Relevance
“…Tuina, acupuncture, and Chinese herbs have direct analgesic effect, but lumbar traction performs its work slowly [37] and does not have direct analgesic effect, so in all outcome measurements the efficacy of lumbar traction was the worst. Additionally, Tuina and acupuncture can exert an immediate analgesic effect [38, 39], so their effectiveness in invalid rate and cure rate was also better than Chinese herbs.…”
Section: Discussionmentioning
confidence: 99%
“…Tuina, acupuncture, and Chinese herbs have direct analgesic effect, but lumbar traction performs its work slowly [37] and does not have direct analgesic effect, so in all outcome measurements the efficacy of lumbar traction was the worst. Additionally, Tuina and acupuncture can exert an immediate analgesic effect [38, 39], so their effectiveness in invalid rate and cure rate was also better than Chinese herbs.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, 45 acupuncture reviews (28 of which also searched Chinese databases) included studies in both Chinese and in other languages (331/352 = 94% of which were in English). Twenty-one of these reviews that included only Chinese-language trials and nine reviews [48][49][50][51][52][53][54][55][56] that did not include any Chineselanguage trials in the forest plots of binary outcomes were excluded from the quantitative analysis (Appendix Table 2). The remaining 15 [20,[57][58][59][60][61][62][63][64][65][66][67][68][69][70] acupuncture reviews included both Chinese-and non-Chinese-language studies in the forest plots of binary outcomes and were included in the quantitative analysis.…”
Section: Characteristics Of Acupuncture Reviewsmentioning
confidence: 99%
“…Cerezo-Téllez et al ’s study on 130 non-specific neck pain patients showed that DN can effectively reduce pain intensity, mechanical hyperalgesia, neck active angle of motion and muscle strength at 1, 3 and 6 months postoperatively 6. Several meta-analysis results also supported the use of DN, especially deep DN, in the management of chronic MPS 10–12. Cagnie et al reviewed 15 randomised controlled trials including approximately 800 patients and concluded that there was a strong evidence for DN to have a positive effect on pain intensity 10.…”
Section: Introductionmentioning
confidence: 99%